Rekonstruksi Teologi Kesetaraan Gender dalam Pemikiran Fatimah Mernissi dan Mansour Fakih - Azkia Faiqotun Ni’mah; Muhamad Aldi; Farichatul Maftuchah (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
Gender inequality in Islamic societies often stems from patriarchal interpretations of religious texts. This research aims to analyze and compare the gender liberation theology of two prominent Muslim intellectuals, Fatimah Mernissi and Mansour Fakih. Utilizing a literature study method with comparative and critical analysis approaches, this study explores how both figures deconstruct the roots of gender inequality. The findings reveal that Fatimah Mernissi emphasizes her struggle on epistemological and historical-philological critiques of misogynistic hadiths, which she identifies as products of "Political/Cultural Islam," in order to restore the egalitarian essence of "Message Islam" (Islam Risalah). Meanwhile, Mansour Fakih focuses his analysis on sociological-structural aspects through the "Theology of the Oppressed" (Teologi Kaum Tertindas). The theological reconstruction offered by Mernissi and Fakih shifts from rigid jurisprudence (fiqh) toward justice-oriented interpretation, positioning human equality as a fundamental principle of Islam